New species of Scolytodes (Coleoptera: Scolytidae) from Costa Rica and Panama - Jordal, Bjarte H (Revista de Biología Tropical, 1998)
Seven species of Scolytodes (tribe Ctenophorini) are described as new to science: S. coneavus and S. circumsetosus (from Fieus branches, La Selva), S. montanus (Monteverde), S. nudifrons (Las Cruces near San Vito), and S. triangulus (fogging sample, La Selva), all from Costa Rica, and S. ungulatus (Cerro Punta) and S. punetífrons (fromAstronium graveolens, Canal Zone), ooth from Panama. New distributional and host plant data are given for the following species: S. amoenus (Fieus branch, La Selva, and the first record south of Mexico), S. immanis (Cerro de La Muerte), S. impressus (Xylopia branch, Peninsula de Osa), S. ochromae (Ochroma branch, La Selva), S. piceus (fogging sample, La Selva, tbe first low altitude record), and S. swieteniae (fogging sample, La Selva and Braulio Carrillo, the first exact locality data), all from Costa Rica, and S. nanellus (Barro Colorado Island) from Panama.